Causes of hospitalization among children ages zero to nine years old in the city of São Paulo, Brazil (Clinics, 2010)
INTRODUCTION: The profile of child morbidity is an important parameter for defining and altering health policies. Studies about infant mortality are more numerous than those on morbidity, especially related to hospital admissions. The objective of this study is to describe the causes of admission in the public health system for children from zero to nine years of age in the city of São Paulo during the years 2002 to 2006 and compare these results to those from the national data. METHOD: Through a cross-sectional study, data were obtained from the Hospital Information System, which is available in the Information System of the Unified Health System - DATASUS. RESULTS: Within the period, 16% of the total admissions corresponded to children from zero to nine years of age, with most of the children being younger than one year of age. In the city of São Paulo, the admission coefficient increased 11%, and in Brazil, it decreased 14%. Respiratory diseases were the main causes of hospitalization. In São Paulo, the second most frequent causes of admission were diseases that originated during the perinatal period (15.9%), and in Brazil, the second most frequent cause of admission was infectious-parasitic diseases (21.7%). Admissions for perinatal diseases increased 32% in São Paulo and 6% in Brazil. While hospitalizations for diarrhea decreased in Brazil, an increase was recorded in the city of São Paulo for children under five years old. CONCLUSIONS: The findings of this study show a paradoxical increase in the number of hospitalizations during an expansion of primary attention, indicating that the rise was not associated with a significant improvement in the quality of service.